(3EMUGA GdYdhes - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3ebGdI ai EMUGA GdYdhe bGd CHh fUQ eMeO Hf eMeO GdaGQGHi QMeg Gddg JYGdi bUOfG ai gPG GdcJGH Cf eMUi GdYdhe GdeTghQI YdekG GdaUd GdChd ai Yde GddSGf Yde GddSGf ai GdLedI VQHGf CMOgeG MaX GdCdaGX GdOGdI YfO CeI s
(3BNQgG (B:s
(3aLGFR Cf jMed GdEfSGf Ydi MW faSg HGdcPH hGdeZGdWI ceG jaYd Pdc HGdfSGA hGdUHjGf Je hGdMeO dhGgH GdYhf hGdYbd cKjQkG ceG gh Cgdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(646/3) s
Keywords: (3GdadSaI hGdefWbs